Patterns of Community Empowerment through Fishermen’s Groups in Improving the Economy on the Pasaran Island of Bandar Lampung - Diana, Diana; Nasor, Nasor; Rosyidi, Rosyidi; Budiwiranto, Bambang; Setiawati, Rini (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2024)
This research is motivated by an interest in the economic empowerment program implemented by the Pasaran Island Fishermen Group, Kota Karang Village, Bandar Lampung City. The purpose of this research is to find out how the pattern of community empowerment through fishermen groups in improving the economy on Pasaran Island, Bandar Lampung. This research uses qualitative methods, namely data obtained by observation, interviews, and documentation. The results of this study indicate that in an effort to develop the economy of fishermen on Pasaran Island, several strategies are used which include education and training patterns, counseling and mentoring patterns, and fisheries business partnership patterns, with the main strategy emphasized is the provision of assistance from the government for fishermen. Empowerment through fishing groups is able to respond to local conditions because what they do gives very positive results and is able to improve the economy of the community on Pasaran Island.